Buddhist monasteries of South Asia and China - Sanjay Garg, Ed (Society for Buddhist Art and Archaeology monograph, 2019)
Buddhism binds the two most populated regions of the world - South Asia and China. In developing a holistic understanding of the historical linkages between these two regions, scientific studies of the Buddhist texts, its monumental and material remains and numerous archaeological sites have played a very important role. The results of recent excavations at many such sites have altered our understanding of monasteries as mere residences for monks and have simultaneously revealed the existence of many important Buddhist centres which were an integral part of the cultural and religious fabric of the society. These excavations have also brought forth the need for studying these sites in a wider religious landscape and network. This volume contains 18 papers that were presented by leading archaeologists and art historians from South Asia and China at an international conference on Buddhist Monasteries in South Asia and China organized by the Society for Buddhist Art and Archaeology (SBAA) in New Delhi in December 2015. These contributions focus on themes such as: newly discovered or worked Buddhist monastery and temple sites in South Asia and China; a comparative study of design of the Buddhist monastery in the two regions; stupas, paintings and sculptures discovered in the Buddhist monastery sites and documents and inscriptions related to the Buddhist monastery and temple. This volume aims to provide fresh insights and information on new sites and place them along with the earlier known ones in a wider cultural landscape. About the Author Sanjay Garg is an eminent scholar with extensive research experience in history of South Asia, with specialization on economic and monetary history, currency and coinage, architecture and archiva